2012
DOI: 10.1088/0004-637x/746/1/85
|View full text |Cite
|
Sign up to set email alerts
|

THEHUBBLE SPACE TELESCOPECLUSTER SUPERNOVA SURVEY. V. IMPROVING THE DARK-ENERGY CONSTRAINTS ABOVEz> 1 AND BUILDING AN EARLY-TYPE-HOSTED SUPERNOVA SAMPLE

Abstract: We present ACS, NICMOS, and Keck AO-assisted photometry of 20 Type Ia supernovae (SNe Ia) from the HST Cluster Supernova Survey. The SNe Ia were discovered over the redshift interval 0.623 < z < 1.415. Fourteen of these SNe Ia pass our strict selection cuts and are used in combination with the world's sample of SNe Ia to derive the best current constraints on dark energy. Ten of our new SNe Ia are beyond redshift z = 1, thereby nearly doubling the statistical weight of HST-discovered SNe Ia beyond this redshif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
1,356
4
23

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,575 publications
(1,454 citation statements)
references
References 113 publications
71
1,356
4
23
Order By: Relevance
“…; ∼200 spectroscopically confirmed Type Ia SNe) and the CFHT Supernova Legacy Survey (SNLS; Astier et al 2006;Conley et al 2011;Sullivan et al 2011; ∼500 spectroscopically confirmed Type Ia SNe in the three-year data set SNLS3). At very high redshifts, HST surveys (Riess et al, 2004Suzuki et al, 2012) have yielded ∼ 25 Type Ia SNe at z > 1.0, which confirm the expectation that the universe was decelerating at high redshift and limit possible systematic effects from evolution of the supernova population or intergalactic dust extinction. At intermediate redshifts (0.1 < z < 0.4), the SDSS-II supernova survey Sako et al, 2008) has discovered and monitored 500 spectroscopically confirmed Type Ia SNe; only the first-year data set (103 SNe) has so far been subjected to a full cosmological analysis (Kessler et al, 2009 present cosmological results from a sample of 752 photometrically classified SDSS-II SNe with spectroscopic host galaxy redshifts, and a joint analysis of the SNLS and SDSS-II samples is in process (J. Frieman, private communication).…”
Section: The Current State Of Playsupporting
confidence: 67%
See 1 more Smart Citation
“…; ∼200 spectroscopically confirmed Type Ia SNe) and the CFHT Supernova Legacy Survey (SNLS; Astier et al 2006;Conley et al 2011;Sullivan et al 2011; ∼500 spectroscopically confirmed Type Ia SNe in the three-year data set SNLS3). At very high redshifts, HST surveys (Riess et al, 2004Suzuki et al, 2012) have yielded ∼ 25 Type Ia SNe at z > 1.0, which confirm the expectation that the universe was decelerating at high redshift and limit possible systematic effects from evolution of the supernova population or intergalactic dust extinction. At intermediate redshifts (0.1 < z < 0.4), the SDSS-II supernova survey Sako et al, 2008) has discovered and monitored 500 spectroscopically confirmed Type Ia SNe; only the first-year data set (103 SNe) has so far been subjected to a full cosmological analysis (Kessler et al, 2009 present cosmological results from a sample of 752 photometrically classified SDSS-II SNe with spectroscopic host galaxy redshifts, and a joint analysis of the SNLS and SDSS-II samples is in process (J. Frieman, private communication).…”
Section: The Current State Of Playsupporting
confidence: 67%
“…Prominent examples include the supernova and weak lensing programs of the CFHT Legacy Survey (CFHTLS; Conley et al 2011;Semboloni et al 2006a;Heymans et al 2012b), the ESSENCE supernova survey (Wood-Vasey et al, 2007), BAO measurements from the Sloan Digital Sky Survey (SDSS; Eisenstein et al 2005;Percival et al 2010;Padmanabhan et al 2012), and the SDSS-II supernova survey . These have been complemented by extensive multi-wavelength studies of local and high-redshift supernovae such as the Carnegie Supernova Project (Hamuy et al, 2006;Freedman et al, 2009), by systematic searches for z > 1 supernovae with Hubble Space Telescope Suzuki et al, 2012), by dark energy constraints from the evolution of X-ray or optically selected clusters (Henry et al, 2009;Vikhlinin et al, 2009;Rozo et al, 2010), by improved measurements of the Hubble constant (Riess et al, , 2011Freedman et al, 2012), and by CMB data from the WMAP satellite (Bennett et al, 2003;Larson et al, 2011) and from ground-based experiments that probe smaller angular scales. 4 Most data remain consistent with a spatially flat universe and a cosmological constant with Ω Λ = 1 − Ω m ≈ 0.75, with an uncertainty in the equation-of-state parameter w that is roughly ±0.1 at the 1 − 2σ level.…”
Section: Looking Forwardmentioning
confidence: 99%
“…We choose 580 SNe Ia data of Union2.1 1 [34] which cover the redshift interval 0.015 ≤ z ≤ 1.414, to constrain the parameters α and η. The Union2.1 compilation is an updated version of Union2 [35] compilation by adding new SNe data from the Hubble Space Telescope Cluster Survey to Union2 compilation.…”
Section: Samplesmentioning
confidence: 99%
“…In Union2.1, they chose H 0 = 70kms −1 Mpc −1 to get M B and µ (see Equation (4) and Table 6 in Ref. [34]). So, in this paper, we must choose H 0 = 70kms −1 Mpc −1 in D-R equation to constrain α and η.…”
Section: Samplesmentioning
confidence: 99%
“…The accelerated expansion is currently widely attributed to the existence of a "dark energy" component, which is compatible with Einsteinʼs cosmological constant. Over the last decade, the sample of SNe Ia has increased dramatically (e.g., Astier et al 2006;Wood-Vasey et al 2007;Bailey et al 2008;Kowalski et al 2008;Balland et al 2009;Freedman et al 2009;Hicken et al 2009;Kessler et al 2009;Amanullah et al 2010;Contreras et al 2010;Suzuki et al 2012;Betoule et al 2014;Rest et al 2014), and it now comprises several hundred spectroscopically confirmed SNe Ia. Since SNe Ia probe the low-redshift universe, they are ideal tools to measure the properties of dark energy.…”
Section: Introductionmentioning
confidence: 99%